Błonowy stan odkształceń w powłokach obrotowych drugiego stopnia o dodatniej krzywiźnie Gaussa - Schlüssler, K.A.; Förster, W. (Engineering Transactions, 1969)
When following the idea prior to Własow to describe the membrane forces of second order surfaces with positive Gaussian curvature as a function of a complex variable using an appropriate transformation of coordinates, the authors succeeded to get on an analogue way the coordinates of the displacement vector. The solution of the corresponding differential equation is possible by simple integration. The special example of a spherical shell loaded by an external couple serves to illustrate the general way.